(untitled) (Bangladesh Journal of Agricultural Research, 2010)
For controlling stemfly (Opheoniyia phaseoli) and pod borers (Helicoverpa armigera & Maruca vitrata of mungbean insecticides Carbofuran, Carbosulfan, and Phenyl Pyrazol were applied as seed treatment and soil application during kharif II season (August to December) in 2004 and 2005 at Burirhat, Rangpnr. In two years, stemfly infested 86.67-93.33 percent rnunghean plants and caused 26.90-27.09 percent stem tunneling in untreated plots. Carbofuran in both seed treatment and soil application had similar effect on stemfly resulting 1.4 to 7.0 and 1.4 to 4.57 times less damage and stem tunneling, respectively, than the control. Pod borer damage did not differ significantly among the treatments in 2004, but differed in the second year. The yield of mungbean was significantly higher by the soil application of Corbofuran followed by the seed treatment by the same insecticides. But soil application of Carbofuran proved to be economical. Key Words: Seed treatment; soil application; insecticides; stemfly; pod borers; mungbean. DOI: 10.3329/bjar.v34i2.5803 Bangladesh J. Agril. Res. 34(2): 303-311, June 2009